Delamination and transverse crack growth prediction for laminated composite plates and shells. (December 2016) - Li, D.H.
Highlights: A VCCT-XLWM method for the delamination and transverse crack was developed. The simultaneous propagation of transverse cracks and delaminations can be predicted. Any complex delamination front can be closely approximate and tracked. Abstract: Based on the extended layerwise method (XLWM) (Li, 2016; Li et al., 2015) and virtual crack closure technique (VCCT), a VCCT-XLWM method is proposed to predict the delamination and transverse crack growth of laminated composite plates and shells. In the VCCT–XLWM method, the laminated composite plates and shells with delamination and transverse crack are simulated by the XLWM method, and the strain energy release rate (SERR) along the delamination front is calculated by the VCCT. The moving delamination front with an arbitrary and changing shape is traced by an algorithm presented by Xie and Biggers (2006), and delamination growth is predicted by a mixed-mode fracture criterion.